2022
DOI: 10.30604/jika.v7i4.1275
|View full text |Cite
|
Sign up to set email alerts
|

Concept Analysis of Self Efficacy Among Coronary Heart Disease Patients Undergoing Percutaneous Coronary Intervention

Abstract: Mortality and morbidity due to coronary heart disease (CHD) are increasing. Patients with coronary heart disease are undergone Percutaneous Coronary Intervention (PCI) have different perceptions regarding these actions so the belief of inability to care for self is different for everyone, therefore, it is important to build the capability of patients which is called self-efficacy. The purpose of this article is to explain the definition of the concept of selfefficacy in CHD patients undergoing PCI. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The average empowerment and self-efficacy of CHD patients in the intervention group were higher than the control group. The results of the study can be concluded that structured health education is effective in increasing empowerment and self-efficacy of CHD patients [11].…”
Section: Supported By Research By Ahn Et Al Whichmentioning
confidence: 88%
“…The average empowerment and self-efficacy of CHD patients in the intervention group were higher than the control group. The results of the study can be concluded that structured health education is effective in increasing empowerment and self-efficacy of CHD patients [11].…”
Section: Supported By Research By Ahn Et Al Whichmentioning
confidence: 88%
“… 14 In the context of CHD, SE means patient’s belief in the ability to manage the signs and symptoms of cardiovascular disease. 15 A low level of SE in CHD patients will result in a lack of self-acceptance, poor health conditions, and the emergence of depressive symptoms. 16 In addition, it is argued that low SE also have a negative effect on self-care, especially in terms of physical activity.…”
Section: Introductionmentioning
confidence: 99%